Ptyx: the word in action - Nascimento, Fabiana Angélica (Lettres Françaises, 2014)
The aim of this study is to present some meanings of the word ‘ptyx’, which first appeared in Mallarmé’s poem Ses purs ongles très haut dédiant leur onyx (known in Brazil as the Sonnet in ix), and which has been fascinating generations of readers and interpreters of Mallarmé. After presenting the meanings, the objective is to relate them and the interpretations of the word to the reading of Mallarmé’s work from the 19th-century to the end of the 20th- century. Then, the purpose is to present an interpretation of the word ptyx in the poem according to the newest criticism about Mallarmé’s work.